Estrangeiros qualificados: a nova face da imigração no Brasil - Momo, Gilda Amaral Carvalho (2014)
In recent years, Brazil has been experiencing frequent influx of foreign professionals seeking work in the country. As a result of Brazil's resilience to the global financial crisis started in 2008, the country has become an increasingly attractive destination for immigrants, constituting a unique opportunity to attract talent in the international market and thus promote the development of the country more effectively. The objective of this dissertation is to study the high-skilled immigration in Brazil in the 21st century. Through survey data obtained from the Ministry of Labour of Brazil (2012) more than 73,000 immigrants arrived in Brazil in the year 2012, which represents an increase of over 50% compared to 2009. Much of this contingent is made up of professionals with higher education and with high technical expertise. They are highly qualified which made them wanted by any transnational company in a globalized world where knowledge is the key requirement to develop a country like Brazil. We intend to analyze these immigrants, their countries of origin, professional activity, in which areas they work in Brazil, gender and level of education. We will start a field research through interviews with immigrants to know about their trajectories, the reasons that brought them to Brazil and their experiences in working in a country so distant and multiethnic. It is therefore an empirical research, exploratory and incorporates bibliographies and surveys of a documentary nature, from which yielded quantitative and qualitative information. The work raises chances that the international economic crisis and social networking were important factors in the decision to migrate to Brazil. Hypotheses that will be confirmed by the search result. Although the phenomenon of skilled immigration is not recent, it is little studied and the dissertation will enrich that study by presenting a single fact in the history of Brazilian immigration with a wealth of amazing data about this new international migratory flow which begins in the 21st century, where high professional qualification requirement determines human mobility on the world stage